Box and cox. (Economist, 1994)
The article discusses the corporate practice of job-sharing. Job-sharing usually means two people splitting a full-time job, generally by working two-and-a-half days each. They split the pay and benefits of a full-time worker-unlike normal part-time workers, who do not enjoy such rights. In the U.S. job-sharing is part and parcel of changes in the workforce. The consensus is that job-sharing works best in highly structured jobs, such as data processing, clerical work and customer-service departments in shops; financial analysis and computer programming may also be good candidates.